Sexual misconduct in academic setting: domestic law and practice in Malaysia - Ali Mohamed, Ashgar Ali (Inderscience Publisher, 2015)
Sexual harassment is one of the contemporary silent issues in academic setting in the schools and institution of higher education. The above subject has become a climax discourse and heatedly debated in various sectors in the recent past. A number of theoretical and empirical studies have demonstrated that sexual harassment has a tendency of causing long term psychological disturbances to the victims. Despite of advocacy of no discrimination between female and male in education, sexual harassment in schools and higher educational institutions in Malaysia is drastically prevalent. This paper therefore explores the domestic laws of Malaysia dealing with sexual misconduct against the students and its adequacy.